The pearls of the crown - Françaix, Jean 1912-1997 (<<The>> Criterion collection, 2010)
"Sacha Guitry plays four roles—including François I and Napoleon III—in this multilingual whirlwind of pageantry investigating the history of seven pearls, four of which end up on the crown of England and three of which go missing. The Pearls of the Crown rockets through four centuries of European history with imaginative, winking irreverence." [criterion.com]
Original: Frankreich 1937
Bildformat 1.33:1
Keywords: Film; DVD-Video